حافظ عبدالسلام کی " تفسیر القرآن الکریم " میں لغوی منہج کا مطالعہ: A Study of the Lexical Methodology in Hafiz Abdul Salam’s " Tafsir-ul-Quran al-Kareem” - Muhammad Irfan; Talib Ali Awan; Shams ul Arfeen (Al-Qamar, 2020)
Translations of the Quran have been written in different languages, but Urdu language is fortunate that most of the translations and commentaries were written in this language. Among these Urdu commentaries a notable commentary is “Tafsir-ul-Quran al-Kareem” written by Hafiz Abdul Salam Ibn Muhammad. This article studies the Lexical Methodology in the mentioned tafsir.